THE STATUS OF A CHILD AFFECTED BY MILITARY ACTIONS: SOME ASPECTS OF LEGAL REGULATION AND APPLICATION PRACTICE - Kmetyk, Khrystyna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article: to analyse some aspects of the legal regulation and practical implementation of the protection of children’s rights in Ukraine during wartime, with a particular focus on the impact of the armed aggression by the russian federation and on the mechanisms for determining and realising the legal status of children affected by military actions and armed conflicts. Research methods: the research applies a combination of formal-legal, comparative and analytical methods, as well as a systemic approach to examining national and international legal frameworks and their application in wartime conditions. Results: the article highlights inconsistencies in national legislation and the lack of coordination among state bodies responsible for protecting the children’s rights. Discussion: an author argues that effective protection of children in wartime requires the revision of existing legislation, harmonisation with international humanitarian and human rights standards, and the introduction of an integrated system of legal and social guarantees for children who have become victims of war.